Supervised internship as a training room of pedagogue’s professionality - Portelinha, Ângela Maria Silveira; Ghedini, Cecilia Maria (Revista Hipótese, 2021)
The National Curriculum Guidelines for the Pedagogy Major sets the curriculum organization must take into account teaching practice, school management, and research. It has generated a need to restructure curriculum components, including internship programs. The present paper problematizes the articulation between teaching practice, school management, and research components in the training process of pedagogue’s professionality. In this sense, we analyze some theoretical-methodological guidelines in the Supervised Internship I of the Pedagogy Major of Western Paraná State University, campus Francisco Beltrao. We present another way of conceiving, organizing, and developing different times and spaces for the treatment of training dimensions.
Keywords: Intership; Pedagogy major; Pedagogue’s professionality; Teacher training